Analisis pengaruh perbedaan koefisien gesekan statis dan kinetis terhadap gerakan stick-slip menggunakan bahan viskoelastis - Zahrul Fuadi (Jurnal Teknik Mesin Indonesia, 2016)
Stick-slip motion in a mechanical system is undesirable because it hasnegative effects on the performances such as positioning errors and excessive wear. Stick-slip motion is caused by various parameters such as the difference between static and kinetic coefficient of friction, âs-âk. In this study, the effect of the difference between static and kinetic coefficient of friction, âs-âk, on stick-slip occurrence is numerically simulated and experimentally tested using a mass-slider system. The objective is to find out the effect of âs-âk parameter on the stick-slip propensity, qualitatively, using viskoelastic material. The results indicated that the amplitude of the stick- slip motion increased significantly with the increased value of âs-âkparameter.